Alkyl−(Hetero)Aryl Bond Formation via Decarboxylative Cross‐Coupling: A Systematic Analysis. Issue 12 (10th February 2017) - Sandfort, Frederik; O'Neill, Matthew J.; Cornella, Josep; Wimmer, Laurin; Baran, Phil S.
Abstract: Suzuki, Negishi, and Kumada couplings are some of the most important reactions for the formation of skeletal C−C linkages. Their widespread use to forge bonds between two aromatic rings has enabled every branch of chemical science. The analogous union between alkyl halides and metallated aryl systems has not been as widely employed due to the lack of commercially available halide building blocks. Redox‐active esters have recently emerged as useful surrogates for alkyl halides in cross‐coupling chemistry. Such esters are easily accessible through reactions between ubiquitous carboxylic acids and coupling agents widely used in amide bond formation. This article features an amalgamation of in‐house experience bolstered by approximately 200 systematically designed experiments to accelerate the selection of ideal reaction conditions and activating agents for the cross‐coupling of primary, secondary, and tertiary alkyl carboxylic acids with both aryl and heteroaryl organometallic species. Abstract : Cross‐coupling meets amide bond formation : Decarboxylative cross‐coupling with redox‐active esters forms C−C bonds using boronic acids, organozinc, and organomagnesium species with simplicity comparable to amide bond formation. The extensive study enables selection of optimal activating agents and conditions across various substrates, including notoriously challenging heteroarenes.